Prevalence of Sexually Transmitted Infections and Predictors for Loss to Follow Up among Marginalized Homeless and Migrant Communities: a Cross-Sectional Study - Francesco Vladimiro Segala; Roberta Novara; Gianfranco Giorgio Panico; Renato Laforgia; Lucia Raho; Marcella Schiavone; Giovanni Civile; Nicole Laforgia; Stefano Di Gregorio; Giacomo Guido; M Cormio; Angelo Dargenio; et al. (2024)
Annals of Global Health is a peer-reviewed, fully open access, online journal dedicated to publishing high quality articles dedicated to all aspects of global health. The journal's mission is to advance global health, promote research, and foster the prevention and treatment of disease worldwide. Its goals are to improve the health and well-being of all people, advance health equity, and promote wise stewardship of the earth's environment. The latest journal impact factor is 2.90. Annals of Global Health is supported by the Program for Global Public Health and the Common Good at Boston College. It was founded in 1934 by the Icahn School of Medicine at Mount Sinai as the Mount Sinai Journal of Medicine. It is a partner journal of the Consortium of Universities for Global Health. From time to time, Annals of Global Health publishes Special Collections, a series of articles organized around a common theme in global health. Recent Special Collections have included "Local evidence and strategies in addressing NCDs Non-Communicable Diseases in Tanzania", "Universal Health Coverage through Integrated Care", and "The Minderoo-Monaco Commission on Plastics and Human Health". Global health workers interested in developing a Special Collection are strongly encouraged to contact the Managing Editor in advance to discuss the project.